Experimental Study of Wear Behavior on Composite Materials under Dry Sliding Conditions - Bima Aditya Wicaksono; Nanda Putri Maheswari (SEED: Journal of Scientific Research, 2026)
Dry sliding wear is a critical failure mechanism in composite materials used in automotive, aerospace, and industrial applications. The increasing use of polymer, metal, and hybrid composites requires a systematic understanding of their tribological behavior under dry conditions. This study experimentally investigates the wear behavior of various composite materials under dry sliding conditions, focusing on the influence of reinforcement type, applied load, sliding velocity, and material composition. A pin-on-disc tribometer was employed to evaluate wear rate and coefficient of friction across different composite systems. The experimental results demonstrate that composites reinforced with ceramic and carbon-based fillers exhibit significantly lower wear rates compared to unreinforced matrices. Hybrid composites show superior wear resistance due to synergistic reinforcement effects. The findings are consistent with previous studies on epoxy, aluminum, magnesium, and polymer-based composites reported in recent tribology literature. The study confirms that reinforcement fraction and operating parameters strongly govern wear mechanisms, transitioning from abrasive to adhesive and delamination wear at higher loads. This research provides practical insights for material selection and design optimization of composite components subjected to dry sliding conditions.